Practical anaerobic broth-disk elution susceptibility test. - Jorgensen, J H (1980)
A modified broth-disk elution method for routine susceptibility testing of anaerobic bacteria was compared with the proposed reference agar dilution method under study by the National Committee on Clinical Laboratory Standards. The broth-disk elution method used a 24-h test incubation period, Schaedler broth medium supplemented with menadione, and GasPak (BBL Microbiology Systems) incubation. Results obtained by this method compared favorably with carbenicillin, chloramphenicol, clindamycin, and penicillin minimal inhibitory concentrations. The 24-h incubation period led to major discrepancies with tetracycline disk elution tests. This method represents a practical routine procedure for testing of anaerobic bacterial isolates in hospital clinical microbiology laboratories.